Penyalahgunaan Lembaga Perkawinan dalam Praktik Poligami Siri: Formulasi Perlindungan Hukum bagi Istri Sah - Albert Tanjung (Universitas Nasional, 2026)
This study aims to analyze the abuse of the institution of marriage in the practice of unregistered polygamy (siri polygamy), as well as to formulate an appropriate legal protection framework with legal certainty for the lawful wife in cases of unregistered polygamy. The analysis is conducted using the theory of legal certainty and the theory of legal protection. This is considered important because the practice of unregistered polygamy formally utilizes the institution of marriage in the name of religious legitimacy, yet substantively aims to circumvent the state's legal control mechanisms over polygamy. This situation positions the lawful wife as a victim, as a result of the legal disadvantages she suffers. This study employs a normative juridical method through statutory, conceptual, and case approaches. The data used are secondary data consisting of primary, secondary, and tertiary legal materials, which are analyzed qualitatively and presented prescriptively. The results of the study show that unregistered polygamy constitutes an abuse of the institution of marriage that causes legal harm to the lawful wife in the form of the loss of her exclusive right as the sole marital partner and her procedural rights in relation to the granting of marriage permits pertaining to the principle of open monogamy as the concept of marriage adopted in Indonesia. The formulation of appropriate legal protection with legal certainty for the lawful wife as the victim of unregistered polygamy lies in the integration of the civil and criminal domains. In the civil domain, unregistered polygamy can be qualified as an unlawful act (onrechtmatige daad) as stipulated in Article 1365 of the Civil Code for the abuse of the institution of marriage. Furthermore, specifically within the realm of Family Law, unregistered polygamy can serve as grounds for filing a divorce lawsuit based on the provisions of Article 19 letter a and letter f of Government Regulation Number 9 of 1975 on the Implementation of Law Number 1 of 1974 on Marriage, in conjunction with Article 116 letter a and letter f of Presidential Instruction Number 1 of 1991 on the Compilation of Islamic Law. In the criminal domain, unregistered polygamy can be qualified as a criminal offense against marriage, adultery, and cohabitation as stipulated in Article Article 402, 411 paragraph (1) in conjunction with Article 412 paragraph (1) and paragraph (2) letter a of Law Number 1 of 2023 on the Criminal Code. Abstrak Penelitian ini bertujuan untuk menganalisa penyalahgunaan lembaga perkawinan dalam praktik poligami siri, serta merumuskan formulasi perlindungan hukum yang tepat dan berkepastian hukum bagi istri sah atas poligami siri. Analisis dilakukan dengan menggunakan teori kepastian hukum dan teori perlindungan hukum. Hal ini dinilai penting karena praktik poligami siri menggunakan institusi perkawinan secara formal atas nama legitimasi agama, namun secara substansial bertujuan menghindari mekanisme kontrol hukum negara terhadap poligami. Keadaan ini menempatkan istri sah sebagai korban, sebagai akibat dari kerugian-kerugian yang diderita secara hukum. Penelitian ini menggunakan metode yuridis normatif melalui pendekatan perundang-undangan, konseptual dan kasus. Data yang digunakan adalah data sekunder dengan bahan hukum primer, sekunder dan tersier yang dianalisis secara kualitatif dan disajikan secara preskriptif. Hasil penelitian menunjukkan, bahwa poligami siri merupakan penyalahgunaan lembaga perkawinan yang menimbulkan kerugian hukum bagi istri sah berupa hilangnya hak eksklusif sebagai satu-satunya pasangan kawin dan hak prosedural sehubungan dengan pemberian izin perkawinan yang berkaitan dengan asas monogami terbuka sebagai konsep perkawinan yang dianut di Indonesia. Formulasi perlindungan hukum yang tepat dan berkepastian hukum bagi istri sah selaku korban dari poligami siri terletak pada pengintegrasian antara bidang perdata dan pidana. Secara perdata, poligami siri dapat dikualifikasikan sebagai perbuatan melawan hukum (onrechtmatige daad) sebagaimana ditentukan dalam Pasal 1365 Kitab Undang-undang Hukum Perdata atas penyalahgunaan lembaga perkawinan. Selain itu, secara khusus dalam tataran Hukum Keluarga, poligami siri dapat dijadikan sebagai alasan untuk mengajukan gugatan perceraian berdasarkan ketentuan Pasal 19 huruf a dan huruf f Peraturan Pemerintah Nomor 9 Tahun 1975 tentang Pelaksanaan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan Perkawinan juncto Pasal 116 huruf a dan huruf f Instruksi Presiden Nomor 1 Tahun 1991 tentang Kompilasi Hukum Islam. Dalam bidang pidana, poligami siri dapat dikualifisir sebagai tindak pidana terhadap perkawinan, perzinaan dan kohabitasi yang ditentukan dalam Pasal 402, Pasal 411 ayat (1) juncto Pasal 412 ayat (1) dan ayat (2) huruf a Undang-undang Nomor 1 Tahun 2023 tentang Kitab Undang-undang Hukum Pidana.